Quality management of Arabic language education at Madrasah Tsanawiyah Negeri 1 Sragen. 2023/2024 academic year. - Rafika, Wahyu Nur; Hafidah, Hafidah (Lembaga Penelitian dan Pendidikan Mandala, 2024)
The aims of this research are: (1). To find out the quality management of Arabic language education according to SNP (in this study using 3 points: content standards, process standards, and graduate competency standards) at Madrasah Tsanawiyah Negeri 1 Sragen. (2). To determine the supporting and inhibiting factors for SNP management at Madrasah Tsanawiyah Negeri 1 Sragen.This research uses qualitative research. The place of this research is at MtsN 1 Sragen. This research was conducted in May 2024 – June 2024. The subjects in this research were Arabic language teachers and school principals. Data collection techniques using observation, interviews, documentation and archive notes.The research results show that: (1). Arabic language learning management at MTs N 1 Sragen includes five stages, namely: planning, organizing, implementing, supervising and evaluating. These stages have been implemented well and are in accordance with national education standards (SNP). (2). Supporting factors for the implementation of SNP in an effort to improve the quality management of education at MTsN 1 Sragen include the geographical location of the school, cohesiveness, readiness and enthusiasm of teachers in teaching, which are supporting factors in the implementation process, while the inhibiting factors are the different student backgrounds, meaning that the students are not all motivated to learn Arabic.